The revolving door to homelessness. The influence of health, alcohol consumption and stressful life events on the number of episodes of homelessness. - Roca, Pablo; Panadero, Sonia; Rodríguez-Moreno, Sara; Martín, Rosa María; Vázquez, José Juan (Anales de Psicología / Annals of Psychology, 2019)
Objectives.- To analyse the impact of different variables on repeated episodes of homelessness. Method.- The study was conducted based on data obtained from a representative sample of homeless people in Madrid (Spain) (n = 188). Results.- Suffering from a serious or chronic illness has an effect on the revolving door to homelessness, which is mediated by a highly negative subjective perception of the individual's own health, which is in turn mediated by suffering from a disability. Excessive alcohol consumption has an effect on the revolving door to homelessness, mediated by access to treatment for problems caused by alcohol consumption. Suffering from a serious or chronic illness correlates with having problems caused by excessive alcohol consumption. Experiencing multiple stressful life events has a direct effect on the revolving door to homelessness. Conclusions.- To prevent the revolving door to homelessness, it is necessary to remove the barriers that hinder access to normal health resources which are experienced by people suffering from social exclusion, while implementing ongoing support programmes for homeless people or those at risk of homelessness, which primarily deal with health issues.